1995
DOI: 10.7164/antibiotics.48.1506
|View full text |Cite
|
Sign up to set email alerts
|

BE-24566B, a New Antibiotic Produced by Streptomyces violaceusniger.

Abstract: In the course of our screening program for new antibacterial compounds, a strain A24566 isolated from a lichen collected at Jyogasaki, Shizuoka prefecture, Japan, was found to produce a potent antibiotic. This compound, BE-24566B (1), was isolated from the mycelial cake of cultural broth, and was shown to have the unique structure in Fig. 1 Characterization of the strain followed the method adopted by the International Streptomyces Project (ISP)1}. The strain A24566 formed well developed and branching substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…It seems that anthrabenzoxocinone compounds might be of special interest among substances isolated from Streptomyces strains. Early studies on Streptomyces violaceusniger, isolated in Japan, led to discovery of a potent anthrabenzoxocinone derivative, named BE-24566B, which might be used against MRSA [28]. Two such compounds were then isolated from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that anthrabenzoxocinone compounds might be of special interest among substances isolated from Streptomyces strains. Early studies on Streptomyces violaceusniger, isolated in Japan, led to discovery of a potent anthrabenzoxocinone derivative, named BE-24566B, which might be used against MRSA [28]. Two such compounds were then isolated from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Without purification, the mixture was further deprotected through hydrogenolysis under catalysis with Pd/C to accomplish the desired target, in racemic form, in 65 % yield over 2 steps. The 1 H NMR, 13 C NMR, and mass spectral data obtained for the synthetic (±)‐ABX, whose structure is further unambiguously confirmed by an X‐ray crystallographic analysis, are in good agreement with those reported for the naturally occurring product …”
Section: Figurementioning
confidence: 99%
“…The results found in the literature for LD 50% in animal models are extremely varied. Kojiri et al (1995) obtained a LD 50% for substance BE-24566B, isolated from Streptomyces violaceusniger, of 100 mg/ml. However, Nakagawa et al (1987) observed that the compound BO-1236, in doses of 2.201 mg/ml, was lethal in 50% of the inoculated animals.…”
Section: Cinnabarin Cytotoxic Effect On Micementioning
confidence: 99%